Differences between SSRI and SNRI in depression treatment - Grego, Mateusz; Grego, Katarzyna; Stojak, Łukasz; Popiela, Dariusz; Urbańska, Karina; Kwiatkowski, Filip; Baczewski, Mateusz; Czyż, Witold (Quality in Sport, 2025)
Introduction Depressive disorders represent a significant health problem worldwide. With the development of pharmacotherapy, selective serotonin reuptake inhibitors (SSRIs) and serotonin-norepinephrine reuptake inhibitors (SNRIs) have become preferred therapeutic options. SSRIs are the most commonly used first-line medications, but there are controversies regarding their efficacy compared to SNRIs. Aim of Study The aim of this study is to analyze the differences between two groups of drugs – SSRIs and SNRIs – in the treatment of depression and to try to identify on this basis a group of drugs that should be used as first-line drugs in the treatment of depression. Materials and Methods This review was conducted by searching scientific publications on PubMed and Google Scholar. The analysis took into account a number of studies comparing individual drugs from both groups of drugs, and then concisely summarized their conclusions. Conclusion The review of the literature and clinical trial results shows that no single universal group of medications can be identified for depression therapy. The choice should be tailored individually to each patient, taking into account the symptoms of their illness and the side effects of previously used medications. At the same time, the review highlighted the need for further research into the types of treatment for depressive disorders.